Representasi Metafora Konseptual dalam Lirik Lagu pada Album Ambivert Karya Raisa: Kajian Linguistik Kognitif Teori Lakoff dan Johnson - Nasution, Naswa Dwi Putri; Lubis, Malan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study examines conceptual metaphors in the lyrics of Raisa's album Ambivert using the cognitive linguistics perspective of George Lakoff and Mark Johnson. This study aims to describe the source and target domains, identify the types of conceptual metaphors, and reveal the representation of meaning contained in the eleven songs on the album. The research data consists of words, phrases, clauses, and sentences containing conceptual metaphors. The analysis was carried out through identifying metaphorical expressions, determining the source and target domains, conceptual mapping, classifying metaphor types, and interpreting the meaning. The results show that there are 106 metaphorical expressions consisting of 74 ontological metaphors, 28 structural metaphors, and 4 orientational metaphors. The resulting representation of meaning includes the search for love, loss, waiting, inner conflict, the struggle to maintain relationships, self-acceptance, and emotional recovery. This finding shows that ontological metaphors dominate the construction of meaning in the lyrics of the album Ambivert, indicating that emotional experiences are mostly conceptualized through concrete entities or objects. This finding strengthens the cognitive linguistics study that metaphor is a conceptual mechanism in understanding abstract experiences, while also demonstrating that conceptual metaphor analysis can be an effective approach to uncovering the structure of meaning and representation of emotional experiences in song lyrics.